2005
DOI: 10.2308/accr.2005.80.4.1125
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure Incentives and Effects on Cost of Capital around the World

Abstract: Prior research predicts that firms reliant on external financing are more likely to undertake a higher level of disclosure, and a higher disclosure level should, in turn, lead to a lower cost of external financing. This paper tests these predictions outside the United States where alternative legal and financial systems could mitigate the effectiveness of such disclosures and, comprehensively, examines both disclosure incentives and disclosure consequences on cost of capital for a common set of firms. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
373
7
57

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 609 publications
(465 citation statements)
references
References 51 publications
28
373
7
57
Order By: Relevance
“…Consistent with this objective, there is extensive research examining how the market as a whole, institutional investors, and analysts respond to more useful and understandable financial disclosures. Specifically, several studies document that higher quality financial disclosures are positively associated with general market liquidity (e.g., Diamond and Verrecchia 1991;Welker 1995;Healy et al 1999), institutional ownership (e.g., Healy et al 1999;Bushee and Noe 2000), analyst forecast accuracy and analyst following (e.g., Barron, Kim, Lim, and Stevens 1998;Lang and Lundholm 1996;Hope 2003), and are negatively associated with the ex ante cost of equity capital (e.g., Leuz and Verrecchia 2000;Easley and O'Hara 2004;Francis, Khurana, and Pereira 2005) and agency costs (e.g., Berger and Hann 2007;Hope and Thomas 2008). SFAC No.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this objective, there is extensive research examining how the market as a whole, institutional investors, and analysts respond to more useful and understandable financial disclosures. Specifically, several studies document that higher quality financial disclosures are positively associated with general market liquidity (e.g., Diamond and Verrecchia 1991;Welker 1995;Healy et al 1999), institutional ownership (e.g., Healy et al 1999;Bushee and Noe 2000), analyst forecast accuracy and analyst following (e.g., Barron, Kim, Lim, and Stevens 1998;Lang and Lundholm 1996;Hope 2003), and are negatively associated with the ex ante cost of equity capital (e.g., Leuz and Verrecchia 2000;Easley and O'Hara 2004;Francis, Khurana, and Pereira 2005) and agency costs (e.g., Berger and Hann 2007;Hope and Thomas 2008). SFAC No.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that lenders are the main source of external financing for private organisations (Koren et al, 2014), they can be labelled as the most important or powerful stakeholder(s) for those. Further, (voluntary) disclosure levels are positively associated with leverage (Hossain et al, 1995;Ahmed & Courtis, 1999) or with the organisation's need for external financing (Francis et al, 2005). Additionally, in accordance with signalling theory, it is expected that organisations with low(er) leverage ratio and a great need for external (debt) financing are more motivated to send signals to the (financial) market about their financial structure and they will consequently disclose more information voluntarily (Khlifi & Bouri, 2010).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 80%
“…However, Francis et al (2005Francis et al ( , p. 1128 note that "there are equity markets in countries with more bank-oriented systems, and, therefore, voluntary public disclosure could still be important as means of accessing equity financing as well as creating greater transparency for private debt financing." Hussainey and Aal-Eisa (2009) have shown that the disclosure of forward-looking information in narratives of the annual reports is an important mechanism for signalling future earnings to professional users such as financial analysts.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations